New Approaches to Antibiotic Therapy for Acute Tonsillopharyngitis in Children - Yu.K. Bolbot (Zaslavsky O.Yu., 2015)
In recent years, a trend for reduced efficacy of treatment for acute tonsillopharyngitis with antibiotics of penicillin group in children has been observed. This is due to the changes in the etiology of the disease: in the genesis of acute tonsillopharyngitis, associations of β-hemolytic streptococcus with Gram-negative and Gram-positive microflora are involved. The use of II generation cephalosporins significantly improves the efficacy of therapy and reduces the risk of complications.